Performance Analysis of Multi-Purpose Fluidic Windows Based on Structured Glass-Glass Laminates in a Triple Glazing - Su, Lingqi; Fraaß, Mathias; Kloas, Matthias; Wondraczek, Lothar (Frontiers in Materials, 2019)
For decades, various technologies have been developed aiming to enhance the energy efficiency of buildings. As a recent example, fluidic windows have been reported which literally enable to wrap buildings into a liquid layer and to transform the building envelope into a thermally active system for energy harvesting, distribution and storage. Elaborating on this concept, we now consider the performance of insulation glass units (IGU) which implement glass-glass capillary panels for liquid circulation. Such devices contain a scalable heat pump that can reversely be operated in active cooling or heating modes. By bridging the insulation panel inside the window, also passive cooling functionality is achieved. Long-term computational performance analysis shows that adequate thermal comfort can be ensured with different window-to-floor size ratios, and for different internal heat gain, for example, caused by differences in room occupation. For a size ratio of 0.4, we demonstrate a competitive seasonal performance factor, i.e., ~ 6.5 for heating and ~ 10.9 for cooling. On-device photovoltaic power can cover more than four fifths or the annual electricity consumption of all auxiliary components. For the size ratio of 0.4 in a highly-occupied office room, the device specific primary energy consumption ensuring year-over thermal comfort is as low as ~ 2.9 kWh/(m2a).